EFEKTIVITAS PEMBERIAN EKSTRAK JAHE TERHADAP PENURUNAN TINGKAT SKOR NYERI MENSTRUASI PADA REMAJA : Studi : Literature Review - Putri Ayniyah Sinta (2020)
Menstrual pain is a problem that often occurs among teenagers. Menstrual pain provides many benefits, challenging is a daily activity and supports the concentration of learning compilations. This literature review aims to elaborate information with evidence based on the field of nursing regarding the effectiveness of giving extra ginger to a score reduction in adolescents that improves menstrual recovery. Methods: research a non-systematic literature review study and search for articles using a database through PubMed, Science Direct, Google Scholar. Obtained 11 journals that have been considered in the criteria: young women who cope with menstrual pain, performed ginger healing therapy, measurement of pain scales using the Numeric Rating Scale and Visual Analog Scale and Experimental research designs, which began to be analyzed. method, namely ginger extract capsules and ginger drinks. Giving a dose of this ginger therapy can be started with the lowest dose. Besides being able to reduce the risk, administration of ginger extract with high doses of 1.5 grams can reduce the hormone prostaglandin. When giving ginger can be done 2 days before menstruation until the disappearance of menstruation is gone. Ginger therapy is effective in reducing menstrual score levels. However, one journal agrees that this is a stitch that cannot be reduced by nausea and vomiting. Keyword: teenager, Primary dysmenorrhea, menstrual pain, ginger extract, pain score.